The Stock Market Relationship between Turkey and the United States under Unionisation - Ugur Ergun,; Abu Hassan Shaari Mohd Nor, (Asian Academy of Management Journal of Accounting and Finance, 2010)
The main aim of this paper is to investigate the dynamic relationship and volatility spillover between the stock markets in Turkey and the United States under the conditions for Turkey's accession to the European Union. This study uses bivariate cointegration, ECM, CGARCH and threshold cointegration for daily data spanning from 1988 to 2008. The presence of nonlinear error correction terms is evaluated using threshold cointegration. Our empirical findings indicate that (a) there were strong dynamic linkages between the Istanbul Stock Exchange and National Association of Securities Dealers Automated Quotation (NASDAQ) after the Custom Union Agreement between Turkey and the European Union was signed, (b) threshold and negative error correction effects exist during the full sample period and (c) significant volatility spillovers exist from NASDAQ to the Istanbul Stock Exchange for the full sample period.